The sandwich-structured advanced high strength steel to resist the liquid metal embrittlement - Wufeng Dong; Hua Pan; Yu Sun; Jiayi Zhou; Ming Lei; Kai Ding; Yulai Gao (Journal of Materials Research and Technology, 2023)
There exists a direct correlation between the alloy elements and the formation of the liquid metal embrittlement (LME) in the advanced high strength steel (AHSS). In the present study, a sandwich-structure AHSS-#2 + IF (Interstitial-free) sheet with the equivalent tensile strength compared with the AHSS-#1 sheet is designed and fabricated to resist the LME cracks. The welded joints with normal structure (RSW joint of galvanized steel AHSS-#1) reveal the higher LME susceptibility than the sandwich-structured one. The maximum length of the detected LME cracks is 1062.9 μm for type I crack (located at the center of the weld) and 152.2 μm for type II crack (located at the shoulder of the weld). Based on the results of the element distribution in the regions near the LME cracks, the internal oxide layer and element segregation are detected for the welded joint with normal structure. The formation of the internal oxide and the element segregation could largely deteriorate the cohesion of the boundaries especially for the region directly contacted with the Zn coating, triggering the formation of the LME cracks. With the protection of the IF steel as the covering layer on AHSS-#2, however, the regions with element segregation are successfully separated from the Zn coating, dramatically decreasing the corresponding LME susceptibility.